CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD): PATHOGENESIS, CLINICAL COURSE AND MODERN MANAGEMENT (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive inflammatory lung disease characterized by persistent airflow limitation that is not fully reversible. It is a leading cause of morbidity and mortality worldwide, primarily associated with long-term exposure to tobacco smoke and environmental pollutants. This study analyzes the epidemiology, pathophysiology, clinical presentation, diagnostic criteria, complications, and modern management strategies of COPD using the IMRAD structure and current evidence-based guidelines.